The American “Positive Attitude” - Eve Bernier-Rock (Angles)
Although American people are perceived as a cultural community with a positive attitude, they are sometimes mocked or criticized in the media for their exaggeration, superficiality, hypocrisy, or being “aggressively friendly.” On the other hand, the French are perceived by American people as complainers, pessimistic, cold, and arrogant. This study brings to light the differences in expressing positive emotions and opinions in French and American social contexts. Through an analysis of authentic conversations collected during “Speed-Friending” events, some language discrepancies will be revealed, so as to be later taught to future foreign language learners in order to reduce bad intercultural perceptions.